Identity and Difference - Ewick, Patricia; Cuba, Lee (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This is a syllabus for a course on Identity and Difference with the following course discription : How can the individual be, at once, cause and consequence of society, a unique agent of social action and also a social product? Why are some people accepted and celebrated for their particular features, while other people and behaviors are considered deviant and stigmatized? This course examines theoretical perspectives on human identity, focusing on processes of creating categories of acceptable and deviant identities. We will discuss how identities are formed, how they vary, the forms and possibilities of unique or aggregate identities, how behaviors are labeled deviant, how people enter deviant roles and worlds, responses to differences and strategies of coping with these responses on the individual and group level. Rather than focus on the differences among various forms of deviant identity and behavior, we will consider the usefulness of various theoretical perspectives that attempt to explain patterns across diverse identities and differences. As we explore the meaning and experience of deviance, we will be simultaneously analyzing conformity. Throughout the course, we will use gender and sexuality as an example of frequently stigmatized forms of identity.